Current Clinical Trials for the Monkeypox Virus - Mahmoud Kandeel (Dr. Sulaiman Al Habib Medical Journal)
Background Monkeypox (MPX) is a zoonotic Orthopoxvirus causing smallpox-like symptoms. Before April 2022, MPX cases outside Africa were rare. The virus can spread through skin-to-skin contact, sexual contact, respiratory droplets, and household items such as towels and blankets. Aim This study was aimed at highlighting the dire need for vaccination and treatment against this infection. Several in-process clinical trials that may help overcome MPX infection are discussed. Methods A search for recent clinical studies was conducted in the clinicaltrials.gov database. Results A total of 15 trials were identified. After February 2022, 14 new trials were launched. Of the 15 trials, 9 were observational studies, 3 were treatment studies and 3 were preventive studies. MPX clinical trial topics were classified into four broad categories: MPX virus shedding and clearance; response to MPX vaccine; antiviral treatment for MPX; and awareness regarding MPX. One medication, tecovirimat, and two vaccines are currently in clinical trials. Conclusions Few treatments and vaccines are under evaluation. Although multiple trials have been conducted, evidence to determine the present state of MPX infection is currently insufficient. Global collaboration is required to achieve complete understanding of the epidemiology, prevention and control of MPX.